Modeling, kinetic, and equilibrium characterization of paraquat adsorption onto polyurethane foam using the ion-pairing technique - Vinhal, Jonas O.; Lage, Mateus R.; Carneiro, Jose Walkimar M.; Lima, Claudio F.; Cassella, Ricardo J. (Journal of Environmental Management, 2015)
We studied the adsorption of paraquat onto polyurethane foam (PUF) when it was in a medium containing sodium dodecylsulfate (SDS). The adsorption efficiency was dependent on the concentration of SDS in solution, because the formation of an ion-associate between the cationic paraquat and the dodecylsulfate anion was found to be a fundamental step in the process. A computational study was carried out to identify the possible structure of the ion-associate in aqueous medium. The obtained data demonstrated that the structure is probably formed from four units of dodecylsulfate bonded to one paraquat moiety. The results showed that 94% of the paraquat present in 45 mL of a solution containing 3.90 × 10^−5 mol L^−1 could be retained by 300 mg of PUF, resulting in the removal of 2.20 mg of paraquat. The experimental data were reasonably adjusted to the Freundlich isotherm and to the pseudo-second-order kinetic model. Also, the application of Morris–Weber and Reichenberg models indicated that both film-diffusion and intraparticle-diffusion processes were active during the control of the adsorption kinetics.
Keywords: Paraquat; Polyurethane foam; Adsorption; Lon-pairing